The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4103/1319-2442.109564
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and consequences of delayed graft function

Abstract: The impact of delayed graft function (DGF) on the outcome of renal transplantation remains controversial. We analyzed the risk factors for DGF and its impact on graft and patient survival. A total of 354 renal transplants performed between June 1986 and April 2000 were analyzed. Variables analyzed included donor and recipient age, method and duration of renal replacement therapy, HLA mismatch, cold and warm ischemia times, biopsy-confirmed acute rejection, length of stay in the hospital, serum creatinine at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
2
27
0
3
Order By: Relevance
“…The incidence of DGF is common in deceased donor transplants compared to living donor renal transplant recipients . With increasing laparoscopic donor nephrectomy and warm ischaemia time, the incidence of ATN has increased .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of DGF is common in deceased donor transplants compared to living donor renal transplant recipients . With increasing laparoscopic donor nephrectomy and warm ischaemia time, the incidence of ATN has increased .…”
mentioning
confidence: 99%
“…4,5 The incidence of DGF is common in deceased donor transplants compared to living donor renal transplant recipients. 6 With increasing laparoscopic donor nephrectomy and warm ischaemia time, the incidence of ATN has increased. 7,8 Serum creatinine, a gold standard biochemical parameter for the laboratory diagnosis of kidney injury, increases late and after significant decline in glomerular filtration rate.…”
mentioning
confidence: 99%
“…Previous studies reported fairly high CIT in some current allocation systems; for example, CIT reported from United States, Turkey, and Tunisia, 21 ± 7, 14, and 18 to 23 hours, respectively (23)(24)(25).…”
Section: Discussionmentioning
confidence: 93%
“…This finding was matched with some reports denoting that slow and delayed graft function are risk factors for T-cell and antibodymediated rejection 19 and the combination of both can affect patient survival. 20,21 Most of our patients were young females, and this was explained by Dörje and associates 2 who found that most of their patients with rejection were young and nonadherent with suboptimal immuno suppression.…”
Section: Discussionmentioning
confidence: 99%